2011
DOI: 10.1590/s0103-64402011000400015
|View full text |Cite
|
Sign up to set email alerts
|

Permanent mandibular incisor with multiple anomalies - report of a rare clinical case

Abstract: Permanent mandibular central incisor is rarely affected by tooth shape anomalies of crown and root. Co-occurrence of multiple anomalies in a permanent mandibular central incisor is extremely rare. This paper reports an unusual concurrent combination of multiple dental anomalies affecting both the crown and root of a permanent mandibular left central incisor -talon cusp, dens invaginatus, short root anomaly and macrodontia -, which has not previously been reported together. Case management is described and impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 18 publications
0
23
0
1
Order By: Relevance
“…An extensive review of English literature yielded only three published cases of isolated non syndromic peg shaped permanent mandibular central incisor, thus making it a rarity (Anziani et al, 2010, Ramachandra et al, 2009, Chanchala et al, 2012. Cases of non syndromic generalized microdontia has also been reported (Bargale et al, 2011, Nagaveni et al, 2011, Nagaveni 2012, Sharma 2001, Ather et al, 2013. Altug -Atac et al, 2007 reported two cases of mandibular peg shaped lateral incisors.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…An extensive review of English literature yielded only three published cases of isolated non syndromic peg shaped permanent mandibular central incisor, thus making it a rarity (Anziani et al, 2010, Ramachandra et al, 2009, Chanchala et al, 2012. Cases of non syndromic generalized microdontia has also been reported (Bargale et al, 2011, Nagaveni et al, 2011, Nagaveni 2012, Sharma 2001, Ather et al, 2013. Altug -Atac et al, 2007 reported two cases of mandibular peg shaped lateral incisors.…”
Section: Discussionmentioning
confidence: 94%
“…To name a few, the peculiarities may vary from microdontia, macrodontia, accessory cusps to hypodontia and hyperdontia. Permanent mandibular central incisor is rarely affected by tooth shape anomalies of crown and root (Nagaveni et al, 2011). Two rare cases of non syndromic peg shaped mandibular central incisor is communicated in this report.…”
Section: Introductionmentioning
confidence: 85%
“…In addition, the dental literature has also reported the association of talon cusps with other odontogenic anomalies such as supernumerary teeth, congenitally missing teeth, dens invaginatus, complex odontoma and impaction 1,[16][17][18] . However, in some cases it may appear as an isolated alteration 8,14,16,19 .…”
Section: Resultsmentioning
confidence: 99%
“…The treatments options include; prophylactic or preventive sealing of the invagination, [17,18] root canal treatment, [19] endodontic apical surgery, [20,21] intentional replantation [22], and extraction [23]. Some authors say there is association between talon cusp and dens invaginatus [18,20].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors say there is association between talon cusp and dens invaginatus [18,20]. Nagaveni et al [18] reported an interesting case showing the occurrence of three unusual anomalies within the same tooth of an Indian patient. These anomalies are talon cusp, dens invaginatus and short root in the lower permanent central incisor which is not reported previously.…”
Section: Discussionmentioning
confidence: 99%